Assessing the relationships between integrative social-rights and human development factors in South-Western Nigeria from the Islamic economics perspective / Oladapo Ibrahim Abiodun - Oladapo Ibrahim, Abiodun (2016)
This study examines and analyses the perceptions of people on the influence of human rights and social justice on the actualization of human development in Nigeria through the constructs of education, health, and income using primary data. The primary data were collected from four (4) rural communities in South-western Nigeria using a cross-sectional technique. In the last few decades, Nigeria has experienced different developmental initiatives such as Millennium Development Goals (MDGs) and National Economic Enhancement Development Strategy (NEEDS) which were tailored towards the enhancement of human development in the country; however, these initiatives have been hindered especially due to injustice and abuse of fundamental social and economic rights. For instance, the development policy in Nigeria caters mostly for the people living in the urban areas while over 50% of the total population living in the rural areas is deprived. This is reflected in the uneven outcomes across geographical and social groups. Prior research in Nigeria has not examined how social justice and human rights influence educational attainment, healthcare delivery, and income distribution in the rural communities using primary data. This study was empirically conducted to fill this gap in the existing literature by assessing the relationships between integrative social-rights (human rights and social justice) (exogenous) and the three contextualized human development factors (education, health, and income) (endogenous) among Nigerian Muslim adults, ages 20 to 49 years living in rural communities. The data were explored in relation to Islamic framework. A total number of 500 survey questionnaires were distributed to collect data from the respondents in the selected rural areas in South-western Nigeria and 384 responses were finally used for the analysis. For data analysis, both SPSS (version 16) and AMOS (version 20) were used. This study found a significant inter-factor relationship between human rights and social justice among the Nigerian rural populace. The study also found that human rights and income and social justice and health explain the variances in human development. Education was found to be an important variable influencing social and economic right, followed by income and then health. Overall, the findings in this study suggest no significant differences in the perception on human development for males and females groups. Although gender was not found to influence human development in this study, it should not be assumed to mean that gender equality in education, income, and health exists in Nigeria. It is widely reported that gender inequality plays a major role in influencing social and economic status. The findings in this study provide the foundation for making further investigations on social justice and human rights factors in order to promote equality and equity in education, income, and health among the Nigerian citizens irrespective of tribal or ethnic and religious affiliations.